2020
DOI: 10.13106/jafeb.2020.vol7.no9.419
|View full text |Cite
|
Sign up to set email alerts
|

Fintech and Banking: Evidence from Vietnam

Abstract: The paper focuses on understanding fintech and the application of fintech in the banking sector in Vietnam. To solve this research objective, the authors analyze fintech development trends, especially the fintech application in the banking sector in Vietnam. To improve the quality of fintech services at banks, the authors conducted consideration of factors affecting customers' intention to use fintech services. To accomplish this, the authors collected data through a survey of 620 customers of the banks locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
8
15
0
Order By: Relevance
“…In this research, PE refers to the degree to which customers are at ease and willing to learn how to utilise the P2P lending platform. In previous studies, scholars have shown a substantial relationship between PE and attitudes toward new technology adoption in fintech and banking [16], smart home application [18], smart application for learning [19], Uber mobile application [20], mobile P2P lending application [12], mobile banking [21]. Furthermore, PE had an impact significantly on PU in new technology adoption intention on mobile learning [22],…”
Section: ) Perceived Usefulnessmentioning
confidence: 98%
See 2 more Smart Citations
“…In this research, PE refers to the degree to which customers are at ease and willing to learn how to utilise the P2P lending platform. In previous studies, scholars have shown a substantial relationship between PE and attitudes toward new technology adoption in fintech and banking [16], smart home application [18], smart application for learning [19], Uber mobile application [20], mobile P2P lending application [12], mobile banking [21]. Furthermore, PE had an impact significantly on PU in new technology adoption intention on mobile learning [22],…”
Section: ) Perceived Usefulnessmentioning
confidence: 98%
“…TAM could be a fundamental model that can be changed or expanded in a variety of ways. As a result, numerous modifications, including other theories, have emerged intending to analyse fintech, as prior researches on mobile P2P lending applications [12], fintech services for bank users [15], and fintech and banking [16].…”
Section: B Hypotheses Development and The Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…E-commerce activity has also grown significantly this year due to the epidemic, with total visits to shopping apps reaching 12.7 billion in the second quarter of 2020 and an increase of 43% quarter-to-quarter. In addition, Vietnamese banks have accelerated digital adoption, partnering with fintech companies to enhance related financial transactions (Nguyen, Doan, & Bui, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One example of the use of information technology in financial institutions is the use of fintech. Lien et al (2020) examines fintech in Vietnam, which is a developing country with a relatively new fintech service. The research results show that fintech services are very important for the banking sector in Vietnam.…”
mentioning
confidence: 99%